2008
DOI: 10.1021/jp801610y
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Barium Titanate and Barium Zirconate in Multilayer Disordered Thin Films at Room temperature

Abstract: The emission of wide band photoluminescence showed a synergic effect on barium zirconate and barium titanate thin films in alternate multilayer system at room temperature by 488 nm exiting wavelength. The thin films obtained by spin-coating were annealed at 350, 450, and 550 degrees C for 2 h. The X-ray patterns revealed the complete separation among the BaTiO3 and BaZrO3 phases in the adjacent films. Visible and intense photoluminescence was governed by BaZrO3 thin films in the multilayer system. Quantum mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…Based on both experimental (such as most recent X-ray absorption studies EXAFS and XANES) of STO as well as theoretical calculations performed by our group, we have now reached a consensus that room temperature PL emission in perovskite based materials originates mainly from their structural disorder at short-range [6,[28][29][30]. Such structural disorder will result in a non-uniform band-gap structure in which electrons or holes may be trapped [29,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Based on both experimental (such as most recent X-ray absorption studies EXAFS and XANES) of STO as well as theoretical calculations performed by our group, we have now reached a consensus that room temperature PL emission in perovskite based materials originates mainly from their structural disorder at short-range [6,[28][29][30]. Such structural disorder will result in a non-uniform band-gap structure in which electrons or holes may be trapped [29,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…These values show good agreement with reference value of BaTiO 3 . BaTiO 3 has a tetragonal crystal system with a = 399.4 pm, c = 403.3 pm; V= 643x10 5 pm 3 [8]. Heat treatment at 1000 o C was applied to CaTiO 3 and CaTiO 3 : Eu 3+ (1% mol), Dy 3+ (1% mol) were applied before SEM analyses were performed.…”
Section: Phase Formation Analysismentioning
confidence: 99%
“…Several titanates are also known to be promising host matrices. The PL investigations of barium titanate have been extensively discussed by Moreira et al [8]. In addition, the PL of several other titanate systems such as gadolinium titanate, zirconium titanate, strontium titanate, lead titanate and calcium titanate, and magnesium titanate are available in the literature [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable room temperature PL effects observed are contributed to both metastable and energetically stabilized defect states formed inside the band gap. Moreira, et al [76] studied photoluminescence of barium titanate and barium zirconate in multilayer disordered thin films at room temperature. The thin films were prepared by spincoating and annealed at 350, 450, and 550 o C for 2 h. It was observed that the wide band emission showed a synergic effect on barium zirconate and barium titanate thin layers in alternate multilayer system at room temperature by 488 nm excitation.…”
Section: (Bi Er) 4 Ti 3 O 12 Luminescent Ferroelectric Thin Filmsmentioning
confidence: 99%